USE OF THE FORCES OF NATURE AS AN ELEMENT OF FORMATION OF GENERAL PERCEPTIONS OF THE CHILD ABOUT PRESERVATION AND PROMOTION OF HEALTH DURING KIEV RUSSIA (X-XIII CENTURY). (Pedagogy of Higher and Secondary Education, 2010)
In the article the author analyses the ways of human's using the recreate natural forces in Kyivan Rus'. It serves as the means of shaping children's general concept of health care and enhancement with the help of body tempering.
Keywords: children's physical development; recreative natural forces; water and sun tempering; swilling; bathing